Predicting Concrete Compressive Strength and Modulus of Rupture Using Different NDT Techniques. (4th December 2014) - Martínez-Molina, Wilfrido; Torres-Acosta, Andrés Antonio; Jáuregui, Juan Carlos; Chávez-García, Hugo Luis; Alonso-Guzmán, Elia Mercedes; Graff, Mario; Arteaga-Arcos, Juan Carlos
Abstract : Quality tests applied to hydraulic concrete such as compressive, tension, and bending strength are used to guarantee proper characteristics of materials. All these assessments are performed by destructive tests (DTs). The trend is to carry out quality analysis using nondestructive tests (NDTs) as has been widely used for decades. This paper proposes a framework for predicting concrete compressive strength and modulus of rupture by combining data from four NDTs: electrical resistivity, ultrasonic pulse velocity, resonant frequency, and hammer test rebound with DTs data. The model, determined from the multiple linear regression technique, produces accurate indicators predictions and categorizes the importance of each NDT estimate. However, the model is identified from all the possible linear combinations of the available NDT, and it was selected using a cross-validation technique. Furthermore, the generality of the model was assessed by comparing results from additional specimens fabricated afterwards.